The fiscal consequences of unrestricted immigration from Romania and Bulgaria - Joakim Ruist (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2014)
When Romania and Bulgaria joined the EU in 2007 Sweden was one of two EU15 countries that did not restrict access to its labor market and welfare systems for Romanian and Bulgarian citizens. This article evaluates the net fiscal contribution in 2011 of Romanian and Bulgarian migrants who arrived in Sweden under this migration regime in 2007-2010. The average net contribution is found to be substantially positive: around 30,000 kronor, or one-sixth of public sector turnover per capita. This result is used to discuss expected corresponding net contributions in other EU15 countries, several of which lifted their restrictions on January 1st, 2014. The United Kingdom and Ireland stand out as two countries that unambiguously have reason to expect even more positive contributions.
Keywords: H20; H50; J61; 330; immigration; welfare benefits; public finances; Romania; Bulgaria; EU